New types of hourly water consumption in small water supply systems - Woyciechowska, Olga; Bergel, Tomasz; Szeląg, Bartosz (Instal, 2023)
In the article, a review of the current state of knowledge on calculating the operational capacity of network balancing tanks was presented. It pointed out, among other things, the lack of reliable hourly water consumption schedules in small water supply systems, which are essential for the correct calculation of the usable volume of network tanks. The aim of this article was to analyze the irregularity of water demand in small water supply systems and to develop new hourly water consumption types based on this analysis. The research conducted in four small water supply systems confirmed that the consumption of water in the systems is subject to hourly fluctuations. It was proven that the type of water consumption during the day differs between non-working days and weekdays, and that there are two peaks of water demand within a day: morning and evening. The morning peak on weekdays, depending on the location, occurred between 7:00-9:00 AM, while on non-working days it was between 9:00-11:00 AM. The evening peak on weekdays was characterized by a broader time range (7:00-10:00 PM), while on non-working days, it was observed between 7:00-9:00 PM. Additionally, it was found that in each of the analyzed water supply systems, the morning peak of water demand on weekdays was lower than the evening peak, whereas on non working days, it was higher than the evening peak.